2018
DOI: 10.1016/j.celrep.2017.12.096
|View full text |Cite
|
Sign up to set email alerts
|

The E3 Ubiquitin Ligase HectD1 Suppresses EMT and Metastasis by Targeting the +TIP ACF7 for Degradation

Abstract: Cancer cells exploit the epithelial-to-mesenchymal transition (EMT) program to become metastatic. Cytoskeletal regulators are required in mesenchymal cells where they promote EMT and EMT-induced migration. In a search for regulators of metastasis, we conducted shRNA screens targeting the microtubule plus-end tracking proteins (+TIPs). We show that the +TIP ACF7 is essential both for the maintenance of the EMT program and to promote migration. We find that the E3 ubiquitin ligase HectD1 promotes ACF7-proteasome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 37 publications
2
50
2
Order By: Relevance
“…Mice carrying the floxed MACF1 alleles (in B6 background) were acquired through a material transfer agreement between the University of Chicago (USA) and the Northwestern Polytechnical University (China). Construction of the targeting vector was reported previously [5], in which the loxP sites were integrated to excise exons 11,12, and 13 of the Macf1 gene (while in the original literature, the flanked exons were reported as E6 and E7) ( Figure S1A). Mice expressing Cre recombinase under the control of Prx1 (paired related homeobox1) promoter (in B6 background) were acquired from Biocytogen Co., Ltd. (Beijing, China).…”
Section: Generation Of the Macf1 Conditional Knockout (Cko) Mousementioning
confidence: 99%
“…Mice carrying the floxed MACF1 alleles (in B6 background) were acquired through a material transfer agreement between the University of Chicago (USA) and the Northwestern Polytechnical University (China). Construction of the targeting vector was reported previously [5], in which the loxP sites were integrated to excise exons 11,12, and 13 of the Macf1 gene (while in the original literature, the flanked exons were reported as E6 and E7) ( Figure S1A). Mice expressing Cre recombinase under the control of Prx1 (paired related homeobox1) promoter (in B6 background) were acquired from Biocytogen Co., Ltd. (Beijing, China).…”
Section: Generation Of the Macf1 Conditional Knockout (Cko) Mousementioning
confidence: 99%
“…Notably, a recent study by Duhamel et al (49) observed that the HECTD1-mediated regulation of ACF7, a +TIPs protein required for cell migration, modulated EMT during metastasis in breast cancer; the decreased expression of HECTD1 promoted ACF7-induced EMT, invasion and metastasis. Thus, the results of the present study, alongside the results from the study by Duhamel et al (49), suggested that HECTD1 may promote EMT through multiple different mechanisms by targeting distinct molecules.…”
Section: Discussionmentioning
confidence: 99%
“…We identified HECTD1 as LXN associating protein. Because HECTD1 is an E3 ubiquitin ligase, which widely involved in the regulation of cancer invasion 37,38 , this prompted us to hypothesis that HECTD1 may be related to the ubiquitylation of IκBα. Interestingly, HECTD1 may interact with adenomatous polyposis coli (APC), whose dysfunction has been linked to the development of most forms of colorectal cancer 39 .…”
Section: Discussionmentioning
confidence: 99%